Terminological Collocation as Object under Study - I. O. Onal (Научный диалог)
The article is devoted to terminological collocations as one of the types of stable word combinations. The main approaches to defining terminological (specialized) collocations based on the works of a number of domestic and foreign authors are considered. The properties of collocations of this type in comparison with the main characteristics of natural language collocations are described. An attempt is made to determine the status of terminological collocations in linguistics. It is shown that distinguishing the terminological collocations in a separate group of lexical units is possible only within a broad approach to the concept of “collocation,” as these word combinations are characterized by varying degree of semantic cohesion of their components. A typology of terminological collocations with their division into term-forming and term-containing is proposed. The main focus is on collocations that are part of the political terminology of the English and Turkish languages with examples from lexicographical sources, as well as national corpora of these languages and special corpora created in the Sketch Engine system.